Improving concrete and mortar using modified ash and slag cements. (2020) - Dvorkin, L. I (Leonid Iosifovich); Zhitkovsky, V; Sonebi, Mohammed; Marchuk, Vitaliy; Stepasiuk, Yurii
No abstract available